Entrepreneurial Orientation in Micro and Small Enterprises of Traditional Food Centers in Bandung, West Java - Margo Purnomo; Erwin Permana; Achsanul Qosasi; Ahmad Fajri Febrian; Asep Miftahuddin (Binus Business Review, 2019)
The research objective was to analyze the determninant factors of Entrepreneurial Orientation (EO) in the Micro and Small Enterprises (MSEs) of the traditional food centers in Bandung. It used the EO dimension at the organizational level. Five dimensions were used to measure the EO level, namely risk-taking, innovativeness, competitive aggressiveness, proactiveness, and autonomy. The questionare’s was distributed to eight MSEs in Bandung. The sample size is 100 employee Structural Equation Model (SEM) analysis techniques with Partial Least Square (PLS) was used to test the samples. This research shows that the EO level in the micro and small enterprises in the traditional food centers in Bandung is at a moderate level. Although EO of MSEs in the traditional food centers in Bandung is in the moderate category, the results of testing on the EO model find out that each EO dimension forms a significant EO construct. The four dominant and recommended dimensions forming an EO construct in MSEs are risk-taking, innovativeness, competitive aggressiveness, and proactiveness. Among the four dimensions, risk-taking is the dominant dimension. It indicates that courage in taking risks in MSEs is a natural characteristic of the EO in the traditional food centers in Bandung.